![\frac{2p + 1}{3} + \frac{p - 1}{2} = 4 \times \frac{1}{2} \frac{2p + 1}{3} + \frac{p - 1}{2} = 4 \times \frac{1}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B2p++%2B++1%7D%7B3%7D+++%2B+++%5Cfrac%7Bp+-+1%7D%7B2%7D++%3D+4+%5Ctimes+%5Cfrac%7B1%7D%7B2%7D+)
Answers
Answered by
4
Answered by
0
3
2p+1
+
2
p−1
=4×
2
1
\frac{4p + 2 + 3p - 3}{6} = 2
6
4p+2+3p−3
=2
7p - 1 = 127p−1=12
7p = 12 + 17p=12+1
7p = 137p=13
p = \frac{13}{7}p=
7
13
Similar questions
Physics,
1 month ago
Math,
1 month ago
Computer Science,
1 month ago
Math,
3 months ago
Social Sciences,
3 months ago
Math,
11 months ago